Sequencing of the invasive E. coli strain BEN2908 isolated from poultry: A comparative investigation of genomic regions shared with intestinal and extraintestinal model E. coli strains - Tobias Weber Martins; Angélina Trotereau; Simone Lahnig-Jacques; Maxime Branger; Sébastien Houle; Charles M. Dozois; Daniel Brisotto Pavanelo; Fabiana Horn; Catherine Schouler (PLoS ONE, 2026)
Extraintestinal pathogenic Escherichia coli (ExPEC) cause disease outside the gut and include avian pathogenic E. coli (APEC), a leading cause of bacterial infections in poultry. Among their highly diverse types, strain BEN2908 stands out for its significant invasive ability across various human and avian cell types. Aiming to investigate further aspects of this strain and its plasmid, we sequenced and assembled the complete genome of BEN2908 and compared it to 22 E. coli strains, including other invasive strains such as adherent and invasive E. coli (AIEC) LF82 and NRG857c, by constructing a phylogenetic tree and using web-based characterization software. With these results, we selected eight strains closely related to BEN2908 to perform a ring comparison, including two APEC (APEC O1 and IMT5155), two neonatal meningitis E. coli (NMEC; RS218 and IHE3034), two uropathogenic E. coli (UPEC; 78-Pyelo and CFT073), one commensal E. coli (MG1655) and one adherent-invasive E. coli (AIEC; LF82). This revealed 20 genomic regions (GRs) of interest which were then analysed by CD-Search, BLASTp and KEGG Pathway databases. Many of the genes in these GRs had no previous description but showed similarity to known genes involved in sugar uptake, nitrogen metabolism, and dicarboxylate transport and processing, among other functions. These results were tabulated and used to infer possible pathways that could be involved in ExPEC pathogenesis, highlighting candidate genes that have been overlooked in ExPEC research.